Impact of Preoperative Chemotherapy on Physical Function in Patients With Borderline Resectable Pancreatic Cancer: A Retrospective Study - Ken Kouda MD, PhD; Makoto Asaeda PT, PhD; Yuki Nakashima PT, PhD; Takeya Araki MD; Shinji Kawasaki PT; Ayano Ishida PT, MS; Takumi Nagao PT, MS; Noriaki Maeda PT, PhD; Yukio Urabe PT, PhD; Yukio Mikami MD, PhD (Integrative Cancer Therapies)
Purpose: Preoperative chemotherapy in borderline resectable pancreatic cancer (BRPC) reduces tumor size to enable surgery but may cause physical function decline. This study aimed to examine changes in physical function before and after preoperative chemotherapy in patients with BRPC, and explored factors associated with the change. Methods: This retrospective study included 17 patients with BRPC who underwent preoperative chemotherapy and surgery between January 2020 and December 2021. Physical function was assessed using grip strength and the 6-minute walking test (6MWT). Patients were divided into 2 groups based on changes in physical function: (1) those with maintained physical function and (2) those with reduced physical function. Physical function, treatment duration, and the number of chemotherapy sessions were compared between the groups. Results: Grip strength (24.7 ± 6.8 vs 25.1 ± 6.8 kg, P = .462) and 6MWT (451.8 ± 95.7 vs 470.0 ± 82.5 m, P = .119) showed no significant decline after chemotherapy. On subgroup analysis, the reduced physical function group (6 patients) had significantly more chemotherapy sessions than the maintained group (5.0 ± 2.0 vs 2.0 ± 0.6, P = .042), suggesting that prolonged chemotherapy regimens may increase physical function decline risk due to cumulative toxicity. Conclusion: These findings underscore the need for individualized treatment planning, balancing tumor reduction benefits with physical decline risk, especially in frail patients.